Implementation of Curriculum Management to Improve Education Quality in Public High Schools (SMA Negeri) and Madrasas in South Lampung - Oktarianti, Neti (Mudir : Jurnal Manajemen Pendidikan, 2023)
The low quality of education is one of the main challenges faced by the Indonesian nation today. Various efforts have been made to improve the quality of national education, including the development of national and local curricula, enhancing teacher competence through training, providing books and learning tools, improving educational facilities, and enhancing school management. The research method used in this study is qualitative, and the data collection techniques employed are observation, interviews, and documentation.(1) Curriculum Planning in Improving the Quality of Education in Public High Schools (SMA Negeri) and Madrasah involves several steps, such as: a) Comprehensive evaluation of student needs, educational development, and demands of the workforce, b) Collaboration between the Vice Principal, teacher team, and education experts. (2) Implementation of the Curriculum in Improving the Quality of Education in Public High Schools (SMA Negeri) and Madrasah is carried out through: a) Involving training and support for teachers in designing and implementing innovative and relevant teaching methods, b) Encouraging teachers to use active, collaborative, and contextual teaching approaches. (3) Evaluation of the Curriculum in Improving the Quality of Education in Public High Schools (SMA Negeri) and Madrasah is conducted through: a) Continuous and holistic evaluation, b) Assessing the impact of the curriculum, c) Evaluating the Professional Development of Teachers, d) Assessing the effectiveness of innovative teaching methods, improvement of teacher competence, mastery of subject matter, student engagement in learning, and evaluating the impact of the Curriculum program that has been implemented continuously.